Fur color change and hormonal development in captive females of northern white-cheeked (Nomascus leucogenys) and buff-cheeked (Nomascus gabriellae) gibbons - Bolechová, Petra; Chaloupková, Helena; Hradec, Michal; Jánová, Eva; Doležalová, Jana (General and comparative endocrinology, 2019)
Gibbons of the genus Nomascus exhibit strong sexual dichromatism in fur color. Change of fur color in sub-adult wild Nomascus females is associated with the onset of puberty and the time of their dispersal. The variability in fur change may be influenced by social factors. In this study, we determined whether in captive females of crested gibbons begin reproductive maturity prior to dispersing and with association to their fur color. We collected 287 fecal extracts to analyze pregnandiol -3- glucuronide and 17β estradiol profiles of 4 sub-adult females (Nomascus leucogenys and Nomascus gabriellae) and 183 samples from their mothers, using enzyme immunoassays. The sub-adult females were monitored from 4 years of age. Their hormone profiles showed the onset of ovulatory cycling between 4.6 and 5.8 years. Based on the information about the estrogen influence to the secondary sex characteristic (fur color of female) the positive link between estrogen concentration and age of the sub-adult females was found. However, the amount of the estrogen can apparently be influenced by the presence of mother. If the mother was presented, the level of estrogen was higher than if the mother was missing. Our findings suggest that the probability of changing to beige fur color by the sub-adult females increased with increased age and if they were without mother. This initial study presents the maternal influence as a possible social factor affecting the fur color change of female offspring.
Keywords: Animals; zvířecí srst; Female; Hylobatidae; Animal Fur; ženské pohlaví; Aging; pigmentace; Sexual Maturation; Pigmentation; estrogeny; menstruační cyklus; Estrogens; Male; Hylobates; stárnutí; zvířata; mužské pohlaví; pohlavní dospělost; Menstrual Cycle